B-UMCS: Blockchain-enabled Unified Medical Consultancy Service. - Albatoul Almohana; Iman Almomani; Walid El-Shafai (PLoS ONE)
The advent of blockchain technology within the healthcare domain has signified a paradigm shift, transitioning from an emerging trend to an essential infrastructure component that ensures decentralization, transparency, integrity, and persistent availability. Despite its potential, the healthcare sector has not fully capitalized on the vast array of benefits blockchain technology offers. Most existing works utilized blockchain technology within a specific healthcare entity's services but not among several healthcare organizations. They notably lack the provision for direct communication and knowledge transfer between doctors from different hospitals. Therefore, this paper introduces a pioneering Blockchain-based Unified Medical Consultancy Service (B-UMCS) that leverages blockchain's robustness to revolutionize telehealth services by (a) alleviating the shortage of medical expertise through facilitating the interconnection of physicians from diverse hospitals and geographical areas onto a consolidated platform, (b) promoting the seamless sharing of medical consultations, electronic health records (EHRs), and expert insights while upholding rigorous security and privacy protocols, (c) integrating the inherent security mechanisms of blockchain with the distributed data storage functionality offered by the Interplanetary File System (IPFS). This work details the B-UMCS's components, interactions, smart contracts, protocols, algorithms, storage and transmission of EHRs, and their corresponding implementations. The evaluations of the proposed B-UMCS reveal that it secures and facilitates the sharing of EHRs and enables healthcare professionals to collaborate and exchange expertise seamlessly across institutional boundaries. They are additionally ensuring that healthcare providers can offer their knowledge in an efficient and scalable manner. Overall, B-UMCS not only addresses the current challenges in healthcare data security and accessibility but also opens new avenues for collaboration and knowledge sharing among healthcare professionals, ultimately contributing to improving patient care quality.